Pengaruh Promosi Digital terhadap Keputusan Pembelian Produk Kopi Kenangan pada Prodi Manajemen Stambuk 2023 Universitas Negeri Medan - Nazwa Aulia Putri; Indah Sapitri Manurung; Muhammad Ilham Fiqri; Lija Tanjung Manalu; Enzi Anatasya Br Sembiring; Nurul Wardani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study analyzes the influence of digital promotion on the purchasing decisions of 2023 cohort students of the Management Study Program at Universitas Negeri Medan in buying Kopi Kenangan products. The research addresses the increasing reliance on digital marketing among young consumers and the need to understand how online promotional strategies shape their purchasing behavior. A quantitative method with an associative approach was used, involving 100 respondents selected from a population of 935 students through the Slovin formula. Data were collected using a structured Likert-scale questionnaire and analyzed through simple linear regression after the normality and linearity assumptions were met. The results indicate that digital promotion has a positive and significant effect on purchasing decisions, with a regression coefficient of 0.456 and a significance level of 0.000. This finding demonstrates that more engaging, clear, and interactive promotional content is strongly associated with a higher likelihood of students purchasing Kopi Kenangan products. Overall, the study highlights the essential role of digital promotion in influencing consumer decisions, particularly among students who are active users of online platforms. The findings suggest that businesses need to continuously enhance their digital promotional strategies to maintain relevance and strengthen consumer engagement.